Combined influence of food availability and agricultural intensification on a declining aerial insectivore. Issue 3 (21st June 2022) - Garrett, Daniel R.; Pelletier, Fanie; Garant, Dany; Bélisle, Marc
Abstract: Aerial insectivores show worldwide population declines coinciding with shifts in agricultural practices. Increasing reliance on certain agricultural practices is thought to have led to an overall reduction in insect abundance that negatively affects aerial insectivore fitness. The relationship between prey availability and the fitness of insectivores may thus vary with the extent of agricultural intensity. It is therefore imperative to quantify the strength and direction of these associations. Here we used data from an 11‐year study monitoring the breeding of Tree Swallows ( Tachycineta bicolor ) and the availability of Diptera (their main prey) across a gradient of agricultural intensification in southern Québec, Canada. This gradient was characterized by a shift in agricultural production, whereby landscapes composed of forage and pastures represented less agro‐intensive landscapes and those focusing on large‐scale arable row crop monocultures, such as corn ( Zea mays ) or soybean ( Glycine max ) that are innately associated with significant mechanization and agro‐chemical inputs, represented more agro‐intensive landscapes. We evaluated the landscape characteristics affecting prey availability and how this relationship influences the fledging success, duration of the nestling period, fledgling body mass, and wing length as these variables are known to influence the population dynamics of this species. Diptera availability was greatest within predominately forested landscapes, while within landscapes dominated by agriculture, it was marginally greater in less agro‐intensive areas. Of the measured fitness and body condition proxies, both fledging success and nestling body mass were positively related to prey availability. The impact of prey availability varied across the agricultural gradient as fledging success improved with increasing prey levels within forage landscapes yet declined in more agro‐intensive landscapes. Finally, after accounting for prey availability, fledging success was lowest, nestling periods were the longest, and wing length of fledglings were shortest within more agro‐intensive landscapes. Our results highlight the interacting roles that aerial insect availability and agricultural intensification have on the fitness of aerial insectivores, and by extension how food availability may interact with other aspects of breeding habitats to influence the population dynamics of predators.